2012
DOI: 10.1002/hfm.20370
|View full text |Cite
|
Sign up to set email alerts
|

A software‐based method for ergonomic posture assessment in automotive preproduction planning: Concordance and difference in using software and personal observation for assessments

Abstract: This article describes the pilot study for testing a system for ergonomic posture assessment.1 The software‐based approach for ergonomic assessment is based on motion capturing work tasks using realistic mock‐ups of the assembly environment. The approach for ergonomic assessment reduces the expenditure of time for evaluation. This may lead to considerable ergonomic aspects during the early stages of production planning. A comparative test between human observers and the software system was carried out. The tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Usually, the motion capture setup time is about 20 min, but still this method is considered more efficient than any other tool or technology (Klippert, Gudehus, Zick, 2012). However, there is no a unique opinion about the motion capture systems and digital human models.…”
Section: Motion Capture Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…Usually, the motion capture setup time is about 20 min, but still this method is considered more efficient than any other tool or technology (Klippert, Gudehus, Zick, 2012). However, there is no a unique opinion about the motion capture systems and digital human models.…”
Section: Motion Capture Technologymentioning
confidence: 99%
“…Designing a vehicle for production requires conditions and capabilities to ensure the large volume of production, recruiting the required number of employees (Faraway & Reed, 2007). Though the automotive industry is rather advanced, variety of parts and details used for the vehicle production are made and produced manually, which significantly affect the ergonomics (Klippert, Gudehus, Zick, 2012). A large number of studies have shown that proper ergonomics can not only improve the workers' health but also have a positive economic impact on the company (Fritzsche, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations